Nanomaterials: electromagnetic wave energy loss - Melvin Gan Jet Hong; Yaofeng Zhu; Qing-Qing Ni (Springer, Cham, 2019)
The utilization of electromagnetic (EM) wave energy for various appliances and tools in GHz frequency range, in accordance to the development of advanced technology, is rapidly progressing. Simultaneously, the development and research related to EM wave absorbing/shielding materials is also growing fast, in order to cut off and to defend human beings and electronic devices from excessive or unnecessary EM radiation exposure. Nanomaterials is one of the ideal EM wave absorber material, due to their properties such as lightweight, remarkable electrical properties, strongly absorb EM waves, possess tunable absorption frequency, and multifunctionality. This chapter provides introduction of EM wave absorbers; introduction of EM wave energy loss that is highly associated with EM wave absorption performance; discussion on influence factors that affect EM wave absorption capability; and reviews on research and fabrication process of nanomaterials related to EM wave absorber.